2021
DOI: 10.1039/d1nj00086a
|View full text |Cite
|
Sign up to set email alerts
|

Integration of an aminopyridine derived cobalt based homogenous cocatalyst with a composite photocatalyst to promote H2evolution from water

Abstract: Inexpensive cocatalysts are promising material to improve the performance of photocatalytic systems. However, a cocatalyst can be anchored on photosensitizer in certain amount and further loading can hinder the visible...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Using molecular cocatalysts in composite photocatalytic systems to capture more photogenerated electrons from photosensitizers might be a promising strategy. Irfan et al (2021) showed that the homogenous cocatalysts (aminopyridine derived Co-complex) have led the way for increased electron capturing from photoexcited composite photocatalysts (CdS/Ni 3 C), and they offer a lot of potential for improving photocatalytic performance for low-cost H 2 evolution under visible light. Nanoparticles have become popular as homogenous photocatalysts due to their enhanced features, such as a large surface-to-volume ratio, regulated uniform particle size and composition which enhances the degradation rate (Padmanaban et al, 2016).…”
Section: Homogenous Photocatalysismentioning
confidence: 99%
“…Using molecular cocatalysts in composite photocatalytic systems to capture more photogenerated electrons from photosensitizers might be a promising strategy. Irfan et al (2021) showed that the homogenous cocatalysts (aminopyridine derived Co-complex) have led the way for increased electron capturing from photoexcited composite photocatalysts (CdS/Ni 3 C), and they offer a lot of potential for improving photocatalytic performance for low-cost H 2 evolution under visible light. Nanoparticles have become popular as homogenous photocatalysts due to their enhanced features, such as a large surface-to-volume ratio, regulated uniform particle size and composition which enhances the degradation rate (Padmanaban et al, 2016).…”
Section: Homogenous Photocatalysismentioning
confidence: 99%
“…Hugo Schiff, a German scientist and Nobel Prize laureate, prepared the first of these condensation products from primary amines and carbonyl compounds in 1864. , The Schiff base is a structural counterpart of a ketone or aldehyde that has had the carbonyl group (CO) replaced with an imine or azomethine group . Schiff bases are very vital due to their ease of synthesis, availability, and electrical characteristics, particularly in the synthesis of metal complexes via azomethine nitrogen. , Schiff base coordination chemistry has gotten a lot of interest because of its important functions in analytical chemistry, metal refining, organic synthesis, metallurgy, electroplating, and photography. , Schiff bases not only play an important role in advanced coordination chemistry but also are equally significant in bioinorganic chemistry . They have a wide range of medical uses due to their pharmacological characteristics because of the presence of an azomethine (CN) linkage .…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] Based on denticity and stability, the Schiff bases are also very attractive chelators and can form complexes with almost all kinds of transition metals. [14][15][16] The coordination complexes of the Schiff bases derived from 2-aminophenol have gotten a lot of attention because of their widespread application in a variety of biological fields like antibacterial, antifungal, antitumor, nematocide, and antiphlogistic. [17] In addition, these complexes play an important catalytic role in a variety of reactions.…”
Section: Introductionmentioning
confidence: 99%